THE EFFECT OF PROFESSIONAL SKEPTICISM, ETHICS AND COMPETENCE ON THE ACCURACY OF GIVING AN AUDIT OPINION - Ullan Uchi Ramanda; Rahmasari Fahria; Agus Maulana (Berkala Akuntansi dan Keuangan Indonesia, 2022)
The focus of this research is to see how professional skepticism, ethics, and competence on the accuracy of giving an audit opinion. The auditor at the South Jakarta Public Accounting Firm is the study's sample. The sample methodology used was purposeful sampling. The sample for this study consisted of 88 respondents from 19 public accounting firms in South Jakarta. The data used in this study is primary data, in the form of a questionnaire given to the auditor. The hypothesis of this study was tested using Multiple Linear Regression Analysis with Statistics Program and Service Solution (SPSS) version 25 and a significance level of 5%. The study's findings suggest that professional skepticism, ethics, and competence have a positive significant effect on the accuracy of giving an audit opinion.